Pengaruh Etos Kerja, Budaya Organisasi dan Motivasi Terhadap Kinerja Pegawai Kantor Camat Bilah Hulu Kabupaten Labuhanbatu - Aliani, Anggi Nur (Jurnal Manajemen Akuntansi (JUMSI), 2021)
The purpose of this study was to determine the effect of work ethic, organizational culture and motivation on the performance of employees of the Head Office of the upstream bar Labuhanbatu Regency partially or simultaneously. Data collection using interviews and questionnaires. Execution of data analysis methods using a sample of 42 employees. The results of the study based on the F test showed that work ethic (X1), organizational culture (X2) and motivation (X3) simultaneously have a positive and significant effect on employee performance (Y), where the value of F count (10.303) > F Table (2.85) and the significance level of 0.00 < 0.05. The results of partial hypothesis testing (t test) showed that work ethic (X1) has a positive and significant effect on employee performance (Y), where the value of thitung (2.729) > ttable (2.024) and the significance level of 0.008 < 0.05. Organizational culture (X2) has a negative and insignificant effect on employee performance (Y), where the value of the count (-0.993) < ttable (2.024) and the significance level of 0.323 > 0.05. Motivation (X3) has a positive and significant effect on employee performance (Y), where the value of the count (4.265) > ttable (2.024) and the significance level of 0.000 < 0.05. Employee performance is influenced by work ethic, organizational culture and motivation by 11.7% and the remaining 88.3% is influenced by other studies that are not in thorough.